Psikoterapi Islam untuk Penyembuhan Penderita Gangguan Jiwa di Pondok Pesantren Al-Hikmatul Qur’an Kecamatan Kedondong Kabupaten Pesawaran (Jurnal Bimbingan dan Konseling Islam, 2020)
The purpose of this study was to determine the process and methods of Islamic psychotherapy for mental disorders at the Al-Hikmatul Qur'an Islamic Boarding School, Kedondong District, Pesawaran Regency, which is a rehabilitation boarding school specifically intended for people with mental disorders with the aim of helping santri with mental disorders using Islamic approach. This research includes field research with a qualitative approach and is descriptive analysis. Sources of data in this study were 1 ustadz therapist and 1 assistant therapist, 1 administrator and 1 patient's family. The data collection method used was observation, interview, and documentation method. The data analysis technique uses interactive data analysis. The results of research from the implementation of Islamic psychotherapy were carried out with the initial interview stages, the therapy process, action and ending therapy. While the first method with faith and security includes the knowledge of syari'at and riyadloh kubro, the two methods of worship include prayer, dzikir, and prayer.